PHENOMENOLOGICAL STUDY: QUALITY OF LIFE OF ADOLESCENT WITH CANCER - Lina Dewi Aggraeni; E. Sri Indiyah; Indriati Kusumaningsih (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2015)
Introduction. Adolescent is a period growth and development between children and adult. Cancer diagnosed at adolescent age can made them under pressure and full of stress. The aim of the study was to explore a deeper description about quality of life of adolescent with cancer. Method. The study used phenomenology descriptive design with purposive sampling. In-depth interview was held on six adolescent with cancer. Transcript verbatim was analyzed using Colaizzi. Result. The themes were dimension of physical, cognitive, psychology, social, adaptive coping mechanism, and hope. The study concluded that adolescent with cancer dealing with many changing on quality of life but some can build adaptive coping mechanism with their condition and increased their quality of life. Discussion. Child nurse have a big role to increase quality of life of adolescent with cancer by giving a holistic and comprehensive nursing care.Keyword: adolescent, cancer, quality of life, phenomenology